The Effect of Mineral and Biofertilization and Nano-Iron on the Growth and Yield of Broad Bean (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2024)
Background  Beans are an important seed legume crop and are a staple food for millions of people in poor countries. With the increasing demand, there is a large gap between production and consumption of the bean crop. The study aims to investigate the impact of fertilization on the growth and yield of beans.Material and method: During the spring of 2023-2024, scientists performed a field experiment in the Muwailiha region, Babil Governorate. Using three fertilizers the first factor represents Mineral fertilization at three levels (0, 50, and 100)% of the fertilizer recommendation, and the second factor EM1 biofertilization at three levels.  The third factor is spraying with Nano-iron at three levels, using a randomized complete block design (RCBD). Result: The 50% treatment significantly exceeded the fertilizer recommendation for mineral fertilizer and gave the highest average characteristics of plant height, number of pods, and number of seeds per pod. The total yield of the plant is (103.46 cm, 21.52 pods -1, 4.61 seed pods -1, g of plants-1, and 193.72 g) respectively. moreover,  treatment without adding mineral fertilizer gives the lowest averages. The triple intervention treatment (50% fertilizer recommendation + spraying nano-iron at 2 g L-1 +   EM1   20 gL-1) excelled significantly and gave the highest averages for all the studied traits.Conclusion:Using the treatment 50% of the fertilizer recommendation for mineral fertilizer was significantly superior in addition to the triple intervention treatment and gave the highest averages for all the studied traits.